Prenatal Gentel Yoga As Non-Pharmacological on The Anxiety Level in The Third Trimester of Pregnancy - Sri Yolanda Daud; Widia Shofa Ilmiah; Rifzul Maulina (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Anxiety in third trimester primigravida is a common problem and can have an impact on maternal and fetal health. One method that can be used to reduce anxiety is prenatal gentle yoga, which is known to provide a relaxing effect and improve the emotional well-being of pregnant women. The aims to analyze prenatal gentle yoga as Non-pharmacological on the anxiety level in the third trimester of pregnancy. Using quasi-experimental design and pretest-posttest design with a control group. The study sample consisted of third trimester primigravida who were divided into an intervention group (prenatal gentle yoga) and a control group. Anxiety levels were measured before and after the intervention using validated instruments. Data analysis was performed using the Wilcoxon Signed Ranks test to test for differences in anxiety before and after the intervention in each group. The results showed a significant difference in anxiety levels before and after prenatal gentle yoga in the intervention group with a p value = 0.000. Meanwhile, in the control group, there was no significant difference in anxiety levels with a p value = 0.180. Prenatal gentle yoga has a significant effect in reducing the anxiety level of third trimester primigravida. Therefore, prenatal gentle yoga can be recommended as one of the non-pharmacological methods to reduce anxiety in pregnant women.